Strategy and Structure (Book). - Krooss, Herman E.; Zeff, Stephen A. (The Accounting Review, 1963)
Reviews the book "Strategy and Structure: Chapters in the History of the Industrial Enterprise," by Alfred D. Chandler Jr.